Malignant Lesion on Intraoperative Frozen Section with Histopathology Feature Alveolar Soft Part Sarcoma: A Case Report - Wildanur, Sri; Aswiyanti Asri; Pamelia Mayorita (HM Publisher, 2024)
Background: Alveolar soft part sarcoma (ASPS) are slow-growing inert soft tissue masses, but fast-growing masses are also reported. Because the cancer tissue is rich in blood vessels, distant metastasis is easy to occur through the blood tract, and lung metastasis is the most common. The diagnosis of ASPS should be combined with histopathology examination because of its rarity and often misdiagnosed, especially in unusual sites. Case presentation: A 22-year-old female came to the oncology surgery polyclinic at Dr. M. Djamil General Hospital Padang with a chief complaint of a lump in her left thigh since 1 year ago and has been getting enlarged in the last 6 months. The lump has been painful for the last 2 months. Upon an intraoperative frozen section examination, it was concluded that the lesion was malignant. Then, the tissue was prepared from formalin fixed paraffin embedded (FFPE), and the lesion was diagnosed as alveolar soft part sarcoma. Conclusion: In the case of ASPS, surgical management has an important role. The goal of the intraoperative frozen section of this patient is to determine whether the lesion is benign or malignant. There is a need for histological examination, collaboration, and optimal communication between pathologists and surgeons to avoid limitations and pitfalls examination.